2021
DOI: 10.3233/jad-210058
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on Dose-Dependent Effects of Transcranial Photobiomodulation on Brain Electrical Oscillations: A Potential Therapeutic Target in Alzheimer’s Disease

Abstract: Background: Transcranial photobiomodulation (tPBM) has recently emerged as a potential cognitive enhancement technique and clinical treatment for various neuropsychiatric and neurodegenerative disorders by delivering invisible near-infrared light to the scalp and increasing energy metabolism in the brain. Objective: We assessed whether transcranial photobiomodulation with near-infrared light modulates cerebral electrical activity through electroencephalogram (EEG) and cerebral blood flow (CBF). Methods: We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Thus, the reduction in this metric could be attributed to a significant reduction in global integration (as reflected by a reduction in GE) and/or a significant increase in global segregation of the brain network caused by tPBM. These observed significant effects of tPBM on SW taking place only in Stim2 could result from the resistance of resting-state networks against changes in network composition as well as the dose-dependent nature of tPBM-induced effects on neural activity [89,90]. However, a possible explanation for the lack of significant alterations in synchronization and GE in Stim2 could be the high variability in the functional topography of the frontoparietal network [78].…”
Section: Tpbm-induced Alterations In Global Measures Of Functional Ne...mentioning
confidence: 98%
“…Thus, the reduction in this metric could be attributed to a significant reduction in global integration (as reflected by a reduction in GE) and/or a significant increase in global segregation of the brain network caused by tPBM. These observed significant effects of tPBM on SW taking place only in Stim2 could result from the resistance of resting-state networks against changes in network composition as well as the dose-dependent nature of tPBM-induced effects on neural activity [89,90]. However, a possible explanation for the lack of significant alterations in synchronization and GE in Stim2 could be the high variability in the functional topography of the frontoparietal network [78].…”
Section: Tpbm-induced Alterations In Global Measures Of Functional Ne...mentioning
confidence: 98%
“…However, research on the mechanism of tPBM-evoked electrophysiological effects in the human brain is on its early stage with only a handful of publications ( Berman et al, 2017 ; Vargas et al, 2017 ; Zomorrodi et al, 2019 ; Ghaderi et al, 2021 ; Spera et al, 2021 ), besides ours ( Wang et al, 2017 , 2019 ), in the last 4–5 years. Most of these studies have reported alterations of electroencephalography (EEG) powers by tPBM compared to sham stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In patients suffering from either chronic stroke or Alzheimer’s disease, both of which have abnormally functioning networks, photobiomodulation could strengthen and influence functional connectivity within the default mode network itself, together with its connectivity with other networks, for example the salience and central executive networks ( Chao, 2019 ; Naeser et al, 2019 ). In essence, in these damaged and/or diseased states, photobiomodulation may help correct the imbalance of functional connectivity, restoring the connectivity between cortical areas to “normal” levels ( Saltmarche et al, 2017 ; Chao, 2019 ; Naeser et al, 2019 ; Zomorrodi et al, 2019 ; Spera et al, 2021 ). These improvements in functional connectivity manifest in improvements in cognition and memory in, for example, Alzheimer’s disease patients ( Lim, 2014 ; Berman et al, 2017 ; Saltmarche et al, 2017 ; Chao, 2019 ; Baik et al, 2021 ).…”
Section: Photobiomodulation and Wakefulnessmentioning
confidence: 99%